Identification of The Dimensions of Bank 4.0 Experiential Quality Based on Millennial Customer Perceptions - luthfi abdillah; Ananda Sabil Hussein; Kusuma Ratnawati (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
The development of the Bank 4.0 industry that is reflected through increased experiential quality, which is started with the identification of the dimensions of Bank 4.0 experiential quality is getting popularity for millenial. This research attempt to discover the dimensions of Bank 4.0 experiential quality based on perceptions of millennial customers. Bu surveying 673 millenials and adjusted to the characters of Bank 4.0 and millennial generation this study aims to theoretical and empirically testing the hyotehesis by using SMPLS. Results revelaed that functional quality, convenience, innovations, trust, value, risk mitigation, and security have been empirically proven as dimensions of Bank 4.0 experiential quality based on millennial customer perception.This research was only conducted in the city of Malang, so that research with larger demographic and geographic data sets is needed in order to describe the perceptions of millennial customers more accurately. Further research can be developed with new dimensions that may emerge along with the development of Bank 4.0 in both commercial banks and fintech companies.